2010
DOI: 10.1002/sia.3370
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of the anodic films formed on titanium and its Ti‐6Al‐4V alloy in HBr solution

Abstract: The electrochemical properties of anodic oxide films formed on titanium were compared with those on its Ti-6Al-4V alloy. Under potentiostatic anodization in HBr solution over the range 0.20-1.2 V, the current density recorded in the case of Ti was always lower than that for its alloy. The electrochemical impedance spectroscopy results indicate that anodization stimulates higher oxide formation efficiencies, with Ti exhibiting stronger propensity to form thicker passivating oxide layers. The thickness of galvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The apparent activation energies reported in the literature for pure Ti in acidic solutions show high deviation as illustrated in Table IV. [14][15][16]18,39,44,45,[57][58][59][60][61] Relatively higher E a values have been re-ported by earlier studies. For example, Kelly et al 45 demonstrated that E a of Ti in 1 M H 2 SO 4 and 1 M HCl, determined from i m , are 59.9 and 57.3 kJ mol −1 , respectively.…”
Section: Influence Of Temperature On the Anodic Process-passivationmentioning
confidence: 58%
See 1 more Smart Citation
“…The apparent activation energies reported in the literature for pure Ti in acidic solutions show high deviation as illustrated in Table IV. [14][15][16]18,39,44,45,[57][58][59][60][61] Relatively higher E a values have been re-ported by earlier studies. For example, Kelly et al 45 demonstrated that E a of Ti in 1 M H 2 SO 4 and 1 M HCl, determined from i m , are 59.9 and 57.3 kJ mol −1 , respectively.…”
Section: Influence Of Temperature On the Anodic Process-passivationmentioning
confidence: 58%
“…Rauscher et al, 18 Krýsa et al, 58 and Utomo et al 16 also found similar values that calcultated from i corr or i m for Ti in H 2 SO 4 , while Mogoda et al 15 determined the value of 28.1 and 29.7 kJ mol −1 for pure Ti in 0.5 M H 2 SO 4 and 5 M HCl, respecetively. Ghoneim et al 60 reported a value as low as 17.9 kJ mol −1 for Ti in 1 M H 3 PO 4 . In the present work, E a values, which are 27.2 and 22.0 kJ mol −1 calculating from i corr and i m , are comparable with the results of Mogoda et al 15 The lower activation energy as compared with the earlier studies in H 2 SO 4 may be due to the existance of fluoride in the electrolyte.…”
Section: Influence Of Temperature On the Anodic Process-passivationmentioning
confidence: 98%
“…The capacitance (r) of the electrode is described in this region of frequencies, along with the dielectric properties of any film present on the electrode surface. At low frequencies (f < 10 Hz), the process of charge transfer (kinetics of the redox reaction), mass transfer (diffusion or ion migration) and/or other processes carried out on the interface or within the porosities of the metallic surface can be evaluated [36,37]. The results shown in Figure 1 represent the characteristic behaviour of Ti6Al4V (with surface passivation) under all conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of chloride and sulfate ions on the corrosion behavior of Ti and Ti–6Al–4V alloy in oxalic acid medium was also examined . Moreover, the electrochemical properties of thin oxide films formed in HBr solutions potentiostatically on Ti and its Ti–6Al–4V alloy was compared . In general, Ti exhibits stronger propensity to form thicker passivating oxide layers with higher stability than its alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, an impressive amount of literatures on corrosion of Ti alloys are documented . Although, most of them are studied in physiological solution, few studies are carried out in sea water, acid, and other solutions.…”
Section: Introductionmentioning
confidence: 99%